Treatment of post bleaching demineralization using resin infiltration technique: A case report - Nidiaty, Angelia C.; Dwiandhany, Wahyuni S.; Nugroho, Juni J.; Hikmah, Noor; Natsir, Nurhayaty; Trilaksana, Aries C. (Hasanuddin University, 2023)
Objective: This helps minimize the look of discoloration by refracting light just like normal teeth. It also stops further demineralization by strengthening and hardening the enamel.Methods: A 20- year- old male patient came to the Dental Hospital of Hasanuddin University with teeth that had turned yellow since the patient routinely consumed coloured drinks every morning and evening, 3 years ago. In-office bleaching with 40% hydrogen peroxide was done to get the teeth discoloured to become brighter.Results: After application of resin infiltration, it was observed that the resin-infiltrated surfaces of the teeth showed a uniform shade of color and harmonization with the surrounding enamel.Conclusion: Minimally invasive treatment with resin infiltration technique was effective to treat white spot lesions after bleaching treatment.